The Study of Seismic Hazard in Near-Fault Areas Using Probabilistic and Deterministic Approach - Grisella Aglia; Martin Wijaya; Paulus Pramono Rahardjo (Journal of the Civil Engineering Forum, 2023)
Earthquake is one of the most common natural disasters in Indonesia and usually destroys both high and low-rise buildings as well as triggers liquefaction and Tsunami. This means it is important to provide a robust building design with the ability to resist earthquake load and other induced phenomena. One of the methods commonly used to determine the relevant response spectrum of the bedrock is seismic hazard analysis which can be either Probabilistic Seismic Hazard Analysis (PSHA) or Deterministic Seismic Hazard Analysis (DSHA). The application of PSHA allows the representation of the response spectrum of an earthquake using the return period, thereby providing the engineers with the flexibility of selecting the appropriate natural period. Meanwhile, DSHA is based on geological observations and empirical data that can be easily understood. This research discussed the greater influence of seismic hazard analysis on the bedrock response spectrum of near-fault areas including Bandung situated at a distance of 12.9 km from Lembang Fault, Palu at 3 km from Palu Fault, and Yogyakarta at 8.5 km from Opak Fault. Moreover, EZFRISK Program was used to generate a response spectrum at bedrock and the results showed that PSHA is consistently more conservative than DSHA. It was also noted that there are significant differences at shorter periods for Palu site but these differences were observed at the natural period between 1s and 2s for Bandung and Yogyakarta sites.